Scaling of the powder compaction process. (July 2018) - Moghaddam, Majid; Darvizeh, Rooholamin; Davey, Keith; Darvizeh, Abolfazl
Highlights: A method is introduced for scaling of powder compaction process for the first time. Discrete and continuum approaches are utilised for numerical experiments. Inexact scaling of DPC model can predict results with less than 10% error. Inexact scaling in MPFEM has the potential of predicting up to 98% accurate results. Substantial reduction in computational cost achieved using inexact scaling in MPFEM. Abstract: Scaled experimentation plays an important role in the analysis of many material processes and is particularly critical to powder compaction and related processes. A peculiar uncertainty with scaling is the extent to which scaled compaction is representative of the full-scale, powder-compaction process. Although it is possible to perform compaction experimentation combined with simulation using discrete and continuum models applied to both scaled and unscaled processes, this only provides limited insight and does not provide a systematic means to assess the limitation of scaling. A new approach to scaling has appeared in the recent literature, which is founded on the distortion of space making it now feasible to systematically evaluate the effects of scaling on powder-compaction processes. This paper examines numerically discrete and continuum models along with experimental evidence to provide scaling rules for practical use. Correction curves are presented in the paper to correct for scaling effects in scaled experimentation. Graphical abstract: